Research and practice priorities in pilonidal sinus disease: a consensus from the PITSTOP study - Lee, MJ; Lee, E; Bradburn, M; Hind, D; Strong, EB; Din, F; Wysocki, AP; Lund, J; Moffatt, C; Morton, J; Senapati, A; Jones, H; et al. (Wiley, 2024)
Aim: Pilonidal sinus disease is a common condition treated by colorectal surgeons. There is a lack of literature in the field to guide optimal management of this condition. As part of the PITSTOP study, we aimed to identify policy and research priorities to provide direction to the field. Method: Patients and surgeons were invited to participate. A ‘So what, now what’ exercise was conducted, informed by data from PITSTOP. This generated statements for research and practice priorities. A three‐round online Delphi study was conducted, ranking statements based on policy and research separately. Statements were rated 1 (not important) to 9 (important). Statements that were rated 7–9 by more than 70% of participants were entered into the consensus meeting. Personalized voting feedback was shown between rounds. A face‐to‐face meeting was held to discuss statements, and participants were asked to rank statements using a weighted choice vote. Results: Twenty‐two people participated in the focus group, generating 14 research and 19 policy statements. Statements were voted on by 56 participants in round 1, 53 in round 2 and 51 in round 3. A total of 15 policy statements and 19 research statements were discussed in the consensus round. Key policy statements addressed treatment strategies and intensity, surgeon training opportunities, need for classification and the impact of treatment on return to work. Research recommendations included design of future trials, methodology considerations and research questions. Conclusion: This study has identified research and policy priorities in pilonidal sinus disease which are relevant to patients and clinicians. These should inform practice and future research.